Pengaruh Profitabilitas dan Likuiditas serta Ukuran Perusahaan Terhadap Struktur Modal Perusahaan Pariwisata, Perhotelan dan Restoran Yang Terdaftar Di Bursa Efek Indonesia - Siahaan, Novitasari Tuani; Asmapane, Set; Lahjie, Anisa Abubakar (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this study is to test and analyze the factors that influence the company's capital structure in the tourism, hospitality and restaurant sub-sector service companies. The factors that will be examined in this study are profitability, liquidity and firm size. This study uses secondary data sourced from the financial statements of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange in 2013-2017 contained in the Indonesian Capital Market Directory (ICMD). Based on sample selection using purposive sampling method obtained 18 sample companies with a period of observation for 5 years. The analytical tool used is multiple linear regression with SPSS software version 24. Based on the test results obtained results that show that profitability has a negative and significant effect on the company's capital structure, liquidity variables have a negative and significant effect on the company's capital structure, while firm size variables have no significanteffect to the capital structure of tourism, hospitality and restaurant companies listed on the Indonesia Stock Exchange.